Comprehensive Headache Experience in Collegiate Student‐Athletes: An Initial Report From the NCAA Headache Task Force. Issue 6 (7th May 2017) - Seifert, Tad; Sufrinko, Alicia; Cowan, Robert; Scott Black, W.; Watson, Dave; Edwards, Bill; Livingston, Scott; Webster, Keith; Akers, David; Lively, Mathew; Kontos, Anthony P.
Abstract : Background: The prevalence of primary headache disorders in the general population provides a unique challenge in the evaluation of headache occurring in the context of sport. Despite a wealth of studies exploring the epidemiology of headache in the layperson, little is known about the prevalence and nature of headaches in collegiate student‐athletes. These scenarios are challenging in the return to play context, as it is often unclear whether an athlete has an exacerbation of a primary headache disorder, new onset headache unrelated to trauma, or has suffered a concussive injury. Purpose: To establish the prevalence and nature of headaches in collegiate student‐athletes. Study Design: Retrospective cross‐sectional survey. Methods: This cross‐sectional survey evaluated the characteristics and prevalence of headache in 834 student‐athletes from four NCAA Division‐I institutions. Because headache occurrence may vary by sport (collision, contact, non‐contact), by sex, and medical history, our sample included male and female athletes in a variety of sports, with differing degrees of contact exposure. The 20 question survey collected data on personal and family history of headache, as well as concussion history. Results: A total of 23.7% (n = 198) of participants reported having a personal history of migraine, 25.2% (n = 210) history of sinus headache, and 12.3% (n = 103) history of tension type headache. Among athletes with a prior history of concussion, 46.3% (n = 25) of females reported a history of migraine, while only 32.2% of males reported history of migraine (χ 2  = 3.421, P = .064). Conclusions: The etiology of increased prevalence of migraine in our study is unclear. Whether this is due to increased awareness of headache disorders, a consequence of contact exposure, or a predisposition for migraine development in this age group remains unclear. Further studies are indicated.